Zooming to the Scene: Higher Education Chaplaincy and Hybrid Digital Care - Rice-Jalloh, K. Monet (Journal of pastoral theology, 2022)
This essay emphasizes the demand within higher education for hybrid residential and digital care from chaplains and the growing necessity for theological education and continuing education that offer literacy of current technological training of digital platforms. While the American religious landscape is shifting away from singular religious preference and identification, for chaplaincy work, it is pivoting – in that our work has always encompassed multi-faceted ways for the human spirit to access meaning and purpose. What is changing is how we project our work and the means for connecting with our constituents. This essay ultimately argues that the digitally hybrid care responses activated by safety protocols to COVID-19 were inevitably coming due to higher education’s engagement with Gen Z and Gen Alpha; and, moreover, that theological training centers should adapt their core curriculum to include basic audio/visual production, and digital emotional intelligence display.